Uncovering the Comparative Efficacy of Antiviral Drugs and Caricapapaya Phytocompound as VP2H inhibitors in Ebola virus: An Insilico Molecular Docking Analysis - Sakina Fatima (International Journal of Bioinformatics and Computational Biology, 2023)
The Ebola virus is a fatal disease that transmits from wild animals to humans. Infected individuals' body fluids such as spit, blood, perspiration, faeces, blood, saliva, breast milk, sperm, or fomites can transmit Ebola. Adhesion to cell membranes and penetration into the host organism are essential aspects in viral growth. The presence of VP24, as well as nucleoproteins and structural proteins, is necessary for nucleocapsid formation and integration. The inhibition of VP24 activity reduces viral spread. As a consequence, in the current investigation, 25 phytocompounds from Carica papaya and 5 anti-viral FDA authorised oral medicines were assessed for their potential as anti-Ebola virus therapy alternatives. The goal of our research was to use Carica papaya phytocompounds (CPP) to target the VP24 protein of the Ebola virus. VP24 is important in the pathogenesis of the Ebola virus because it suppresses the host immune response, allowing the virus to elude detection and multiply rapidly. Phytocompounds were revealed to have much better binding affinity against the VP24 protein in the current study than the five other FDA-approved antiviral medicines.
Keywords: ADMET analysis; Acyclovir; Carica papaya; Ebola virus disease; FDA approved drugs; Nitazoxanide; Oseltamivir; Sofosbuvir; Tenofovir; VP24 protein; molecular docking; phytocompounds